Initial testing (stage 1) of temozolomide by the pediatric preclinical testing program1. Issue 5 (17th January 2013) - Keir, Stephen T.; Maris, John M.; Reynolds, C. Patrick; Kang, Min H.; Kolb, E. Anders; Gorlick, Richard; Lock, Richard; Carol, Hernan; Morton, Christopher L.; Wu, Jianrong; Kurmasheva, Raushan T.; Houghton, Peter J.; et al.
Abstract Background The DNA methylating agent temozolomide was developed primarily for treatment of glioblastoma. However, preclinical data have suggested a broader application for treatment of childhood cancer. Temozolomide was tested against the PPTP solid tumor and ALL models. Procedures Temozolomide was tested against the PPTP in vitro panel at concentrations ranging from 0.1 to 1, 000 µM and was tested against the PPTP in vivo panels at doses from 22 to 100 mg/kg administered orally daily for 5 days, repeated at day 21. Results In vitro temozolomide showed cytotoxicity with a median relative IC50 (rIC50) value of 380 µM against the PPTP cell lines (range 1 to > 1, 000 µM). The three lines with rIC50 values lesser than 10 µM had low MGMT expression compared to the remaining cell lines. In vivo temozolomide demonstrated significant toxicity at 100 mg/kg, but induced tumor regressions in 15 of 23 evaluable solid tumor models (13 maintained CR [MCR], 2 CR) and 5 of 8 ALL models (3 MCR, 2 CR). There was a steep dose response curve, with lower activity at 66 mg/kg temozolomide and with tumor regressions at 22 and 44 mg/kg restricted to models with low MGMT expression. Conclusions Temozolomide demonstrated high level antitumor activity against both solid tumor and leukemia models, but also elicited significant toxicity at the highest dose level. Lowering the dose of TMZ to more closely match clinical exposures markedly reduced the antitumor activity for many xenograft lines with responsiveness at lower doses closely related to low MGMT expression. Pediatr Blood Cancer 2013; 60: 783–790. © 2013 Wiley Periodicals, Inc.